Association of Insulin-Like Growth Factor 2 Apa 1 A820G (rs680) Polymorphism with Thyroid Dysfunction in a Sample Iraqi Patient - Tamara A. Alubaidi (Journal of Global Pharma Technology, 2018)
The research includes genetic study of insulin-like growth factor-II. The results showed a significant change comparing patients with of hypothyroidism with healthy group. The study included 60 people (males and females). Age ranged (20 - 45 years). Divided into 2 groups: The first group consisted of 30 patients (15 males and 15 females) with hypothyroidism .The second group consist of 30 people (15 males and 15 females) as control group. The results showed that individuals with non-homozygous allele AG had hypothyroidism. The aim of the study is to identify the common allele in a sample Iraqi society for hypothyroidism patients. The results showed a non-significant change when compared with the results of hypothyroidism with hyperthyroidism. While in the healthy group, the safety of individuals from any thyroid gland disease, but the genetic study showed that the number is not small also carrying the allele AG heterogeneous and that if anything indicates that these individuals with the allele AG will be vulnerable to thyroid disease during Next years. A pair of primers is designed to amplify exon 3of IGF-II gene and the polymerase chain reaction produced were sequenced to detect mutation.Keywords: Insulin- like growth factor-2, Hypothyroidism, Hyperthyroidism and thyroid dysfunction.